2014
DOI: 10.1186/s13054-014-0644-4
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of invasive arterial pressure monitoring in cardiovascular patients: an observational study

Abstract: IntroductionCritically ill patients and patients undergoing high-risk and major surgery, are instrumented with intra-arterial catheters and invasive blood pressure is considered the “gold standard” for arterial pressure monitoring. Nonetheless, artifacts due to inappropriate dynamic response of the fluid-filled monitoring systems may lead to clinically relevant differences between actual and displayed pressure values. We sought to analyze the incidence and causes of resonance/underdamping phenomena in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
88
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(111 citation statements)
references
References 25 publications
(50 reference statements)
8
88
0
1
Order By: Relevance
“…There is, however, ample evidence suggesting that non-invasively measured MAP is a better indicator of invasive blood pressure than non-invasive systolic blood pressure alone (4547). While to solve this partial discrepancy is beyond the scope of this study, it has been shown recently that the difference of NIBP and invasive arterial blood pressure is clinically negligible in both adults and children with few exceptions (48,49); NIBP continues to be widely used by ICU physicians (50), and NIBP is proportional to intravascular volume during hemorrhage (12). It is furthermore readily and feasibly available to professionals of all levels of experience and causes few complications (51).…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, ample evidence suggesting that non-invasively measured MAP is a better indicator of invasive blood pressure than non-invasive systolic blood pressure alone (4547). While to solve this partial discrepancy is beyond the scope of this study, it has been shown recently that the difference of NIBP and invasive arterial blood pressure is clinically negligible in both adults and children with few exceptions (48,49); NIBP continues to be widely used by ICU physicians (50), and NIBP is proportional to intravascular volume during hemorrhage (12). It is furthermore readily and feasibly available to professionals of all levels of experience and causes few complications (51).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the natural frequency of the catheter system, the other parameter that determines the fidelity of the recorded signal is the damping coefficient. Under-damping can lead to falsely high systolic pressures and resonant ringing of the pressure pulse [2], while over-damping will conversely lead to diminution of the amplitude, loss of details like the dicrotic notch in addition to falsely low systolic pressures.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, no two consecutive pressure cycles have the same systolic and diastolic blood pressures and the concept of beat to beat variability is well-established. Such variations in systolic and diastolic pressures can be appreciated best in an intra-arterial recording using a fluid-filled catheter connected to a pressure transducer, which being a direct measurement of the pressure in the artery may be considered the gold standard for BP measurements [2], provided care is taken to avoid measurement errors due to air-bubbles, blood clots and compliance of the tube in the catheter system. Intra-arterial BP is an invasive method and it is not possible to perform measurements with invasive techniques in routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…All these values are automatically averaged over a 30-second period, as recommended by the manufacturer. To avoid the risk of underdamping or overdamping of the arterial pressure signal and avert the consequent inaccurate determinations, we performed the square wave test in all patients before initiating the study protocol [24]. The hemodynamic data recorded by PRAM ® were transferred on a data card and then exported into a spreadsheet through dedicated software (MOSTCARE Data Card Reader 4.0.11).…”
Section: Protocolmentioning
confidence: 99%